Optimal therapeutic strategies for pineal region lesions - Huang, Li-tian; Wang, Chun-xi; Li, Tang; Wang, Sheng-yong; Zhou, Quan; Tong, Xiaoguang (Frontiers in Neurology, 2023)
BACKGROUND: Removal of pineal region lesions are challenging and therapeutic strategies for their removal remain controversial. The current study was conducted to identify the characteristics and the optimal therapeutic strategies for pineal region lesions.Methods: This retrospective study reviewed the treatments of 101 patients with pineal region lesions. And different characteristics and therapeutic strategies were shown.RESULTS: There were no statistical differences in the total resection ratio, complication and prognosis outcome between hydrocephalus group and non-hydrocephalus group, except patients in hydrocephalus group were younger. And pediatric had an increased level of intracranial infections. Treatments of lesions and hydrocephalus secondary to pineal region lesions were two integral parts to therapeutic strategies. For management of lesions, Germinoma or Non-germinoma were diagnosed preoperatively, and resection or diagnostic radiation were chosen to deal with pineal region lesions. Endoscopic-assisted surgery provided higher total resection rate. For management of hydrocephalus, ETV had the better therapeutic effect for hydrocephalus. And CSF diversion before radiotherapy or resection did not promote prognosis outcome, but it was necessary for patients with severe hydrocephalus. Logistical regression analysis indicated that age, lesion size, reoperation ratio, and intracranial complications were predictors for prognosis outcome in a developing country.More attention should be paid to intracranial infections in pediatrics with hydrocephalus secondary to pineal region lesions, and CSF diversion before radiotherapy or resection did not promote prognosis outcome, but it was necessary for patients with severe hydrocephalus. Age, lesion size, reoperation ratio, and intracranial complications may be the predictors for prognosis outcome. Most important, surgical algorithm for pineal region lesions which was bases on preoperatively diagnosis (Non-germinoma and Germinoma) was useful, especially in a developing country.